2016
DOI: 10.1515/ppb-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Sniffing the mood for cooperation: Personality and odor induced affective states effects

Abstract: Abstract:The paper explores situational and dispositional underpinnings of cooperative behavior. According to psychological research, cooperation is strongly related to affective states (Forgas, 1998) and personality dimensions (Volk, Thöni, & Ruigrok, 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Sensory environmental cues enhance interpersonal dynamics, as well as pro-social, and cooperative behavior (Forgas, 1998). Experimental studies have found that pleasant ambient scents improved agreeableness and several measures of work cooperativity (Baron & Bronfen, 1994;Marchlewska et al, 2016). A familiar scent highly associated with cleanliness has even been shown to promote prosocial behaviors, such as reciprocating trust and charity (Liljenquist et al, 2010).…”
Section: Impacts Of Scent On Social Behaviormentioning
confidence: 99%
“…Sensory environmental cues enhance interpersonal dynamics, as well as pro-social, and cooperative behavior (Forgas, 1998). Experimental studies have found that pleasant ambient scents improved agreeableness and several measures of work cooperativity (Baron & Bronfen, 1994;Marchlewska et al, 2016). A familiar scent highly associated with cleanliness has even been shown to promote prosocial behaviors, such as reciprocating trust and charity (Liljenquist et al, 2010).…”
Section: Impacts Of Scent On Social Behaviormentioning
confidence: 99%